2008
DOI: 10.1002/hipo.20540
|View full text |Cite
|
Sign up to set email alerts
|

Impaired in vivo synaptic plasticity in dentate gyrus and spatial memory in juvenile rats induced by prenatal morphine exposure

Abstract: ABSTRACT:Prenatal morphine exposure induces neurobiological changes, including deficits in learning and memory, in juvenile rat offspring. However the effects of this exposure on hippocampal plasticity, which is critical for learning and memory processes, are not well understood. The present study investigates the alterations of spatial memory and in vivo hippocampal synaptic plasticity in juvenile rats prenatally exposed to morphine. On gestation days 11-18, pregnant rats were randomly chosen to be injected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 61 publications
(62 reference statements)
5
43
0
Order By: Relevance
“…Further studies [48] showed that the expression of SNAP-25, a SNARE protein essential for synaptic vesicle exocytosis, was regulated in the hippocampus after chronic morphine treatment, with a reduction in the formation of a ternary complex of SNARE proteins in hippocampal synaptosomes. More recently, Zhou and his colleagues [49] at the University of Science and Technology of China (USTC) in Hefei reported that prenatal morphine exposure resulted in the alteration of persistent potentiation of the population spike amplitude, but not in the LTP of perforant-dentate gyrus (DG) synapses in vivo, and such enhanced EPSPspike potentiation was attributed to the decreased inhibition caused by a loss of GABAergic neurons in the DG region of juvenile rat offspring (postnatal day [22][23][24][25][26][27][28][29][30][31]. This finding showed additional cellular mechanisms underlying the impaired spatial learning and memory in rat offspring prenatally exposed to morphine, in addition to the known mechanism associated with the reduction of hippocampal LTD and the depotentiation of LTP in the offspring [50].…”
Section: Hippocampal Plasticity Opiate Addiction and Neurological DImentioning
confidence: 98%
“…Further studies [48] showed that the expression of SNAP-25, a SNARE protein essential for synaptic vesicle exocytosis, was regulated in the hippocampus after chronic morphine treatment, with a reduction in the formation of a ternary complex of SNARE proteins in hippocampal synaptosomes. More recently, Zhou and his colleagues [49] at the University of Science and Technology of China (USTC) in Hefei reported that prenatal morphine exposure resulted in the alteration of persistent potentiation of the population spike amplitude, but not in the LTP of perforant-dentate gyrus (DG) synapses in vivo, and such enhanced EPSPspike potentiation was attributed to the decreased inhibition caused by a loss of GABAergic neurons in the DG region of juvenile rat offspring (postnatal day [22][23][24][25][26][27][28][29][30][31]. This finding showed additional cellular mechanisms underlying the impaired spatial learning and memory in rat offspring prenatally exposed to morphine, in addition to the known mechanism associated with the reduction of hippocampal LTD and the depotentiation of LTP in the offspring [50].…”
Section: Hippocampal Plasticity Opiate Addiction and Neurological DImentioning
confidence: 98%
“…Foetal and neonatal exposure to opioids, and in particular chronic exposure to opioids, have been associated with a variety of neuronal changes [20]. There are very few, if any, studies that have specifically examined whether or not short exposure to opioids results in apoptosis.…”
Section: Effects Seen In Animal Studiesmentioning
confidence: 99%
“…Therefore, the decreased performance on the last 2 days for 10 µg/kg group could be explained by a functional interference of the drug. Morphine, another opioid agonist, has been shown to hinder the restructuration of new brain synapses 30. Cognitive deficits could be caused by a change of the gamma-aminobutyric acid-ergic (GABAergic) inhibition that controls neuronal excitation.…”
Section: Discussionmentioning
confidence: 99%